2D Materials: Epitaxial Growth of h‐BN on Templates of Various Dimensionalities in h‐BN–Graphene Material Systems (Adv. Mater. 12/2019). Issue 12 (19th March 2019) - Chen, Xin; Yang, He; Wu, Bin; Wang, Lifeng; Fu, Qiang; Liu, Yunqi
Abstract : In article number1805582, Bin Wu, Yunqi Liu, and co‐workers demonstrate a library of h‐BN epitaxy on graphene–h‐BN templates of various dimensionalities, including a two‐dimensional homo‐/heteromaterial surface and one‐dimensional interfaces of homo‐/heteromaterials. They provide a framework that allows the description of various types of kinetic growth by combined geometric and structural modelling. This work provides a general viewpoint for understanding epitaxial growth in complex systems.